Unexpected Products of Salicylidene-Aminoguanidine Reactions with Metal Ions—Synthesis and Structural Aspects - Mirjana M. Radanović; Ljiljana S. Vojinović-Ješić; Niko S. Radulović; Vidak N. Raičević; Vukadin M. Leovac; Marko V. Rodić (Organics)
Due to the promising characteristics of aminoguanidine Schiff bases, ongoing research focuses on synthesizing and characterizing different compounds of this class to establish structure–property relationships. However, the pronounced alkalinity of the aminoguanidine residue makes isolating its Schiff bases in neutral form challenging. In the reaction of salicylidene-aminoguanidine ([HL]NO3) with a strong base (NaOH), the partially neutralized product of the formula [HL]NO3∙L·H2O was obtained in the form of single crystals. This compound could be considered a cocrystal in which protonated and neutral forms of the Schiff base coexist. Furthermore, the coordinating properties of [HL]NO3 towards zinc and organotin were investigated, and instead of the expected crystals of complex compounds, a novel polymorph of the ligand was obtained. Additionally, the reaction of [HL]NO3, NH4VO3 and salicylaldehyde was carried out to achieve the condensation of the free NH2-group in the aminoguanidinium fragment, targeting a vanadium(V) complex with tetradentate ligand. However, a purely organic compound containing three salicylaldehyde residues and two imine groups, i.e., C21H18N2O3, was isolated. All the obtained compounds were characterized by elemental and spectroscopic analysis, conductometry and SC-XRD analysis. The data were compared to those of similar structures, and the results provide further insight into the properties of these compounds and their future investigation for potential usage.